A comparative study of migratory behaviour while crossing large geographical barriers in three long-distance migratory passerines - Gustafsson,Lydia (2026)
Migratory behaviour explains how individuals or populations perform their migration. In birds this can include nocturnal or diurnal flights, long or short flights as well as low or high flight altitudes and several other behaviours. These behaviours shift throughout the migratory journey and especially when crossing barriers (large geographical areas where birds might have difficulties to find rest and refuel e.g. deserts and oceans). This master thesis examines how three long-distance songbird migrants, the Thrush nightingale (TN; n = 8) Luscinia Luscinia, the Red-backed shrike (RBS; n = 11) Lanius collurio and the Great reed warbler (GRW; n = 10) Acrocephalus arundinaceus perform their migrations and focuses especially on the common barrier: the Mediterranean Sea and Sahara Desert. I was given data from multi sensor data loggers on the three species and analysed the pressure and activity data. I summarized the annual structure of the migratory activity of the species, and the differences between them when crossing the common barrier. All species performed clustered migratory flights which divided the migration into flight segments with major stopovers in between. The TN and RBS migrate longer distances and performed their migration in 6 and 5 segments, respectively. The GRW who migrate a shorter distance used 4 segments. The migratory intensity was higher during the spring migration in the RBS and GRW but not in the TN. A general positive effect of stopover duration on migratory intensity over the barrier was found for all species, but it did not differ between the species. The RBS was also found to have a higher proportion of inactivity in the major stopover before the barrier crossing compared to the other species. The flight altitudes were generally low over Europe and higher over the barrier, the Mediterranean Sea and Sahara Desert for all species, but the flight altitudes also varied over the migratory route. The RBS was found to have significantly lower flight altitudes when crossing the barrier than the other species. All species were found to sometimes prolonged nocturnal flights into daytime and always climbed to higher flight altitudes at these occasions. The GRW performed on average more and longer prolonged flights than the other two species and flew at high altitudes as long as throughout daytime flights. In conclusion, the species differed to some extent in their migratory behaviour during barrier crossings, and most pronounced in their propensity to perform prolonged flights. The observed differences highlight the need for continued migration research to support effective conservation under ongoing environmental change.